Comparative Study between Laparoscopic Common Bile Duct Exploration plus Cholecystectomy versus Endoscopic Retrograde Cholangiopancreatography plus Cholecystectomy for Cholecysto-Choledocholithiasis - Yadav, Rohit Prasad; Purbey, Bibek Kumar; Yadav, Sanjay Kumar; Shrestha, Bhupendra Charan; Paudyal, Nabin; Yadav, Kumari Ragani; Bhattarai, Amit (Birat Journal of Health Sciences, 2022)
Introduction: The management of concomitant gallbladder and common bile duct stones have been debated between both endoscopic and laparoscopic techniques. Objective: The objective of this study is to compare the efficacy, safety, cost and surgical outcomes of laparoscopic common bile duct exploration plus cholecystectomy and endoscopic retrograde cholangiopancreatography plus cholecystectomy. Methodology: This is a comparative interventional study carried out among 62 patients with concomitant gallstones and common bile duct stones. The study population was divided into two groups by simple randomized sampling technique (lottery technique). Group A underwent laparoscopic common bile duct exploration followed by laparoscopic cholecystectomy in one stage (single-staged management). Group B underwent endoscopic retrograde cholangiopancreatography followed by laparoscopic cholecystectomy in second hospital visit (two-staged management). Results: Complete clearance of the stone with a single attempt was achieved in Group A compared to Group B as 8 patients had gone for a second attempt in group B. Post operative pancreatitis was higher i.e. 24(77.41%) in Group B with statically significance (p value <0.005). Other complications like bleeding i.e. 29(93.54% in A and 26(83.87%) in B group, perforation was also noted during the study period that includes 29(93.54%) in B group. The mean operative time was longer in Group A i.e. 130.2 ± 41.5 minutes while in Group B was 78.5± 10.2 minutes which was statistically significant (p <0.001).The cost of procedure was higher for patients undergoing two-staged management. Conclusion: The complete clearance of the stone with a single attempt was achieved in Group A compared to Group B where 8 patients had a second attempt. Also incidence of pancreatitis was higher in Group B and statically significant. Other complications like bleeding perforation was also noted during the study period in B group. The mean operative time was longer in Group A which was statistically significant. However, for those patients with concomitant gallbladder and common bile duct stones, single-staged management consisting of laparoscopic common bile duct exploration and laparoscopic cholecystectomy could be the preferred method of treatment where the expertise and facilities are available.